REPRESENTASI DAN STEREOTYPE KELOMPOK HIJABERS SEBAGAI BAGIAN DARI POP CULTURE - Ghina Novarisa (Jurnal Ranah Komunikasi, 2017)
The aim of this research is to express the representation and stereotypes of the hijab community who call themselves "hijabers community" through the lifestyle and reality values displayed by the group. Hijabers community proclaims itself as the first hijab group in Indonesia. the existence of this group characterizes certain characteristics of course aiming to differentiate themselves from other groups and bring up their social status that is reflected by their lifestyle. Lifestyle is usually the property of people who have middle and upper economic abilities. Therefore their lifestyle becomes prestige for them and creates class. This phenomenon attracts attention to be seen how the actual representation and stereotype inherent in the lifestyle of the hijaber group. The research method used is the discourse analysis method to show the hidden motivation behind a text. The subject of his research was the text produced from the "hijabers community" group, namely print advertisements of several activities carried out and organized by the "hijabers community" group. The result is a lifestyle representation and stereotype inherent in the hijabers "hijabers community" group is a lifestyle pattern of the middle class and above that is more consumptive, teaching us to be consumptive, where the pattern is herded into a part of pop culture.